1998
DOI: 10.1002/(sici)1097-0304(199806)44:2<159::aid-ccd8>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of thrombolytic therapy of lower-extremity acute, subacute, and chronic arterial occlusions

Abstract: Our purpose was to study the effectiveness of thrombolytic therapy in treating acute, subacute, and chronic arterial occlusions in a multicenter retrospective study. Intraarterial urokinase infusion was performed in 235 patients for occluded native arteries. There were 70 (30%) with acute and 26 (5%) with subacute occlusions, and 141 (59%) with chronic symptoms for longer than 3 mo. Complete thrombolysis was achieved in 60 (86%) of the acute, 20 (77%) of the subacute, and 106 (75%) of the chronic occlusions. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 25 publications
0
52
0
1
Order By: Relevance
“…According to our experience in 100% of cases where the infusion with uPA was completed, we obtained a restitution of a certain degree of patency, transforming all occlusions into stenoses, as did other authors (18,19).…”
Section: Discussionmentioning
confidence: 54%
“…According to our experience in 100% of cases where the infusion with uPA was completed, we obtained a restitution of a certain degree of patency, transforming all occlusions into stenoses, as did other authors (18,19).…”
Section: Discussionmentioning
confidence: 54%
“…One published study reported an immediate distal thromboembolic rate of 5.3%, with similar results for acute and subacute versus chronically occluded lesions [10]. A report on peri-operative distal embolization following intervention for chronic iliac artery occlusion gives a rate of 2.9% [11]. Some reports on distal embolization during intra-arterial thrombolysis have reported rates of 8.3–24% [12, 13].…”
Section: Discussionmentioning
confidence: 91%
“…Most preclinical published literature (6,7,11,14,15) examines reperfusion of acute thrombus (<12 h). However, thrombus composition and response to thrombolytic agents change with time (23,33,34). The present study's model had the advantage of reproducing the clinical scenario with respect to graft material, physiology of graft failure, thrombus burden, and maturation.…”
Section: Discussionmentioning
confidence: 99%